Performance of Kampung Unggul Balitbangtan (KUB) Chicken on Household Scale Semi Intensive Maintenance In Swamp Agroecosystem In Ogan Komering Ilir District: Performan Ayam Kampung Unggul Balitbangtan Pada Pemeliharaan Semi Intensif Skala Rumah Tangga Di Agroekosistem Rawa Lebak Kabupaten Ogan Komering Ilir - Sri Harnanik; Rizky Wiraswati (Program Studi Agribisnis Universitas Sumatera Selatan, 2021)
Kampung unggul balitbangtan (KUB) Chicken is described its performance on the maintenance of household scale semi intensitively in the Ogan Komering Ilir district. This paper aims to describe the performance of KUB chickens reared semi-intensively on a household scale in the Lebak swamp diagroecosystem in the Kayuagung area, Ogan Komering Ilir distrcit. Methods The study was conducted by researchers at the Kayuagung Experimental Garden and by farmers. The study at (KP) Kayuagung was carried out twice, namely the 1st trial from February 2020 to April 2020, the 2nd trial from May 15 to December 2020. The result of the period Sensi chickens reaches an avarage 870 g on 68 days and KUB chickens 434-804 g on 74 days. Semiintensitively Chicken KUB showed first laying varies from 5,5 months to 8 months, quite high risk of disease and exhibits sedating properties. The incidence of disease is quite high at the farmer because the quantity and quality of feed is less than optimal and the weather is dominant wet. But if the quality and quantity of feed is fulfilled can produce many eggs.